Caught between ‘Crossfire’ in the Context of Bangladesh - Sakib, A.B.M. Najmus; Rashid, Zarin Tasnim (International Journal of Criminology and Sociology, 2018)
In recent times, the law enforcement agencies of Bangladesh are universally appreciated for their constitutive and plucky attitude to extremist gangs inside the country. Contrariwise, a suspicious incident of a particular form of extrajudicial killing; Crossfire is fading their achievements. Initially, it was a media term, but now widely used to express the murder of a criminal or accused in a gunfight event between members of law enforcement agencies and criminal groups. This occurrence is facing enormous criticisms in the home and abroad and considered as a violation of human rights. Though public notions about these incidents are surprisingly flexible and they consider this for a prognosis to remainder culprits. This paper analyzed the justice idea of both groups; who are for and against this event from a moral philosophical perspective in the context of Bangladesh. Both the utilitarian idea analyzed by Jeremy Bentham (consequences) and John Stuart Mill (individual human rights) echoes the voice of these two distinct groups respectively. However, the article advocates for a distinctive idea of justice known as deontological philosophy proposed by Immanuel Kant. This moral ideology concentrates on universal human rights and keeps the consequences aside. Considering the fact ‘Crossfire’, this paper believed there is no alternative to ensuring justice and enacting moral duty of law enforcement agencies to indemnify security and safety of the citizen of Bangladesh.